2014
DOI: 10.1186/1471-2458-14-983
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic escalation in metabolic syndrome and cardiovascular risk in a Chinese population experiencing rapid economic development

Abstract: BackgroundMetabolic syndrome (MetSyn) increases the incidence of cardiovascular disease. Information on changes in prevalence of MetSyn in developing countries is limited. This study aims to compare MetSyn prevalence and its associated vascular risk over the period between 2002 and 2010 in a population which has had the world’s fastest economic development over the past three decades.MethodsTwo health surveys were conducted by using the multistage cluster random sampling method in a Chinese population of 85 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 31 publications
2
56
1
1
Order By: Relevance
“…The MS is considered a problem of worldwide proportions, affecting both developed and underdeveloped countries, in a rapidly progressive way [ 15 ]. The present study’s prevalence of MS in Tunisia was higher than those reported in other populations in Oman (21 %) [ 16 ], and Iran (33.1 %) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MS is considered a problem of worldwide proportions, affecting both developed and underdeveloped countries, in a rapidly progressive way [ 15 ]. The present study’s prevalence of MS in Tunisia was higher than those reported in other populations in Oman (21 %) [ 16 ], and Iran (33.1 %) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…China is the largest low-income and middle-income country and has the largest population in the world. With rapid economic growth and changes in lifestyle, such as dietary habits and physical activity,8 the epidemiological data indicate that individuals with overweight and obesity have a higher prevalence of traditional diseases, including dyslipidaemia, hypertension, cardiovascular disease, insulin resistance or diabetes, fatty liver disease and psychosocial complications and some cancers 5 9. Located in northwest China, Xinjiang is an autonomous minority ethnic region within the People’s Republic of China, and one of the fastest developing regions in China.…”
Section: Introductionmentioning
confidence: 99%
“…In their adulthoods, unhealthy lifestyle (smoking, alcohol abuse and high-demanding occupation) and the threat of non-communicable diseases (diabetes, vascular diseases and hypertension) are recognised as major health threats to these cohorts. This is supported by recent studies reporting increasing prevalence of obesity, metabolic syndrome and other non-communicable diseases and their potential associations with changes in lifestyle factors such as westernised eating patterns (Lao et al ., 2014; Mukai et al ., 2014; OECD, 2014). Several of these are known risk factors for dementia and cognitive decline (Norton et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%